2009
DOI: 10.1111/j.1365-2133.2009.09099.x
|View full text |Cite
|
Sign up to set email alerts
|

Hand eczema and quality of life: a population-based study

Abstract: HRQoL was negatively affected in individuals with hand eczema irrespective of age. With the EQ-5D instrument it is also possible to detect certain gender differences. The EQ-5D index for hand eczema was of the same size as for psoriasis and asthma, all common diseases with an impact on public health. It is of importance to acknowledge the influence of hand eczema on daily life, in order to give the patients good care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
138
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(156 citation statements)
references
References 29 publications
(33 reference statements)
9
138
2
3
Order By: Relevance
“…Ten studies, reported in 13 publications, used the EuroQol instrument, and reported either the European Quality of Life-5 Dimensions (EQ-5D) utility score [62][63][64][65][66][67] or the visual analogue scale (VAS) score. [68][69][70][71][72][73] One study reported utilities obtained by the HUI Mark III instrument.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies, reported in 13 publications, used the EuroQol instrument, and reported either the European Quality of Life-5 Dimensions (EQ-5D) utility score [62][63][64][65][66][67] or the visual analogue scale (VAS) score. [68][69][70][71][72][73] One study reported utilities obtained by the HUI Mark III instrument.…”
Section: Resultsmentioning
confidence: 99%
“…74 Three studies used a direct utility elicitation technique. [75][76][77] The 10 studies reported on 28 populations: 14 studies with rhinitis/rhinosinusitis/ rhinoconjunctivitis/asthma, [62][63][64][65][66][68][69][70][71][72][73]78 11 studies with eczema, 67,73,[75][76][77] two studies with food allergy 73,74 and one study with mixed allergies except food allergies. 74 Utility values ranged from 0.5000 for patients with allergic rhinitis receiving allergy vaccination 72 to 0.970 for persons with mild eczema.…”
Section: Resultsmentioning
confidence: 99%
“…As severe chronic hand eczema (HE) causes considerable occupational, social and psychological disability [1,2,3], comprehensive primary prevention strategies at the workplace are needed. The economic and social impact of occupational HE is considerable for both the individual and society.…”
Section: Introductionmentioning
confidence: 99%
“…HE may be disabling and has widespread personal consequences, such as job loss and impaired quality of life (24,25). It is a multifactorial disease, and it is important for patients with HE to know how lifestyle factors may impact on their disease.…”
mentioning
confidence: 99%